(untitled) (Research, Society and Development, 2020)
The constitution of cities mostly occurred in a disorderly manner, converging exponentially to urban conglomerates, characterized by high population concentration, aggressive exploitation of natural resources, including suppression of vegetation, exacerbated consumption (energy; water), excess generation of waste and pollutants, compromising resources and quality of life, promoting stress and environmental deficit. Among the current challenges, urban sustainability stands out, with the city of Salvador-BA, adhering to the Sustainable Cities Program (PCS in Portuguese) and the Sustainable City and Innovation Secretariat (SECIS in Portuguese) was implemented. Thus, it became the focus of this article, which through the documentary analysis of the Management Report (2013-2016) described the main actions of the Sustainability Agenda, in line with the axes, indicators and sustainable practices (PCS). It was observed that there is a strategic demand for better planning, greater transparency, projection of results and organization of a database of the information produced, recording and valuing the actions performed, the continuity process and actions to be performed by SECIS, in a systematic way, being proposed some alternative metrics to the indicators to the actions, in accordance with the local and additive demands to the PCS, triggering management factors and reference of replicability to the municipalities of Bahia.